Kumulacija pokojnine in dohodkov iz opravljanja dela oziroma dejavnosti - Rataj, Primož (Delavci in delodajalci, 2015)
The new Pension and Invalidity Insurance Act (ZPIZ - 2) has brought changes in regard to cummulation of pension and income from employment or self-employment. The core rule is that the pensioner is entitled to up to half of his or her pension if he or she is insured on the basis of part time employment or self-employment. On the other hand, some other legal grounds for work are enacted and presented, which do not have any influence on the payment of pensions. The topic of cummulation is dealt with from various aspects, such as historical development, international documents, comparative legislation of EU Member States and theoretical views of the purpose of pensions.
Keywords: dohodki; plače; pokojnine; pokojninsko zavarovanje